Extreme ocean waves - Pelinovskiĭ, E. N. (Springer, 2017)
This revised and updated℗ℓsecond edition details the vast progress that has been achieved in the understanding of the physical mechanisms of rogue wave phenomenon in recent years. The selected articles address such issues as the formation of rogue waves due to modulational instability of nonlinear wave field, physical and statistical properties of extreme ocean wave generation in deep water as well as in shallow water, various models of nonlinear water waves, special analysis of nonlinear resonances between water waves and the relation between in situ observations, experimental data and rogue wave theories. In addition, recent results on tsunami waves due to subaerial landslides are presented. This book is written for specialists in the fields of fluid mechanics, applied mathematics, nonlinear physics, physical oceanography and geophysics, and for students learning these subjects. Throughout the book, in fact, the reader will find a combination of theoretical and statistical/empirical treatment necessary for the complete examination of this subject. ℓ́Œ Overall, ℓ́ℓExtreme Ocean Wavesℓ́ℓ is a valuable contribution to the literature on wave theory and statistics, helping fill an important gap in our knowledge of a variety of unusual waves. It should be of great interest to scientists and engineers studying physical oceanography, wave dynamics and observations, nonlinear physics, and applied mathematics.ℓ́ℓ ℗ℓ(Eric L. Geist, Pure and Applied Geophysics, Vol. 168, 2011).